Entre nativos e exóticos: a mestiçagem na construção de uma nova identidade na caprinovinocultura dos sertões - Gonçalves Júnior, Oswaldo [UNESP] (My University, 2012)
In the Northeastern Semiarid of Brazil, dynamic among creators of goats and sheep native and exotic bring a range of meanings. In addition to actual trade disputes, conflicts are waged in the realm of ideas, revealing different values and interests around the racial origin of these animals. Between these two segments lies most of the small farmers and the traditional Semiarid sheep and goat raising, based on the use of animals breed, arising from the dynamics of spontaneous crossings, own extensive creations characterized by reduced control over the herds, state which shows a marked contrast to the first two segments. Given that their influence on a traditional creations can result in improved production of small farmers, linked to different social sector research and extension have turned their efforts to construct possible arrangements that are satisfactory to the reversal of historical problems of the region, especially the use of animal miscegenation as a strategy for change. It focuses on the work of these actors, the forms of interaction between them, fulfill the role that ideas, values and attitudes in the face of the possibilities for sheep and goat raising that region.

Na caprinovinocultura do Semiárido, dinâmicas entre criadores de caprinos e ovinos, nativos e exóticos, trazem consigo uma série de significados. Para além de disputas comerciais propriamente ditas, embates se travam no plano das ideias, revelando diferentes valores e interesses em torno da origem racial desses animais. Entre esses dois segmentos situam-se a maior parte dos sertanejos e a tradicional caprinovinocultura do Semiárido, baseada na utilização de animais sem raça definida (SRD), surgidos da dinâmica de cruzamentos espontâneos, próprios de criações extensivas caracterizadas pelo menor controle sobre os rebanhos, estado que revela um acentuado contraste em relação aos dois primeiros segmentos. Tendo em vista que uma influência deles sobre as criações sertanejas pode acarretar uma melhora da produção dos agricultores familiares, diferentes atores sociais ligados ao setor da pesquisa e da extensão rural têm voltado seus esforços para a construção de possíveis arranjos que se mostrem favoráveis à reversão de problemas históricos daquela região, com destaque para a utilização da mestiçagem animal como estratégia para mudanças. Este artigo foca a atuação desses atores, as formas de interação entre eles, o papel que cumprem as ideias, valores e mentalidades em face das possibilidades para a caprinovinocultura daquela região.
Keywords: Sheep and goat raising; Semiarid; small farmers; caprinovinocultura; Semiárido; agricultura familiar